Factores ambientales asociados a rinitis alergica en menores de 15 años atendidos en la clinica medica primavera del distrito de los Olivos en el periodo 2020 - Chilingano Ore, Fiorella Lizerh (2021)
Objective: To determine the environmental factors associated with Allergic Rhinitis in children under 15 years of age treated at the Primavera Medical Clinic in the Los Olivos district in the 2020 period. materials and methods: The following study is analytical, observational, cross-sectional, retrospective, cases and controls. A sample of 302 patients was obtained, 151 cases and 151, all of them were patients under 15 years of age treated at the Primavera Medical Clinic. This information was obtained through the review of archived medical records and statistical data of the morbidity report in the period 2020 in the pediatric service, then it was analyzed using the IBM SPSS version 26 program for Windows 10. Results: Of the 302 patients. The results of this study regarding the characteristic and frequency of allergic rhinitis in children under 15 years of age from the Primavera Medical Clinic; the male gender and the ages of 0-1 year and 2-4 years were those that predominated in the study. Family history is associated with allergic rhinitis, having a p value = 0.00; OR = 2.52. Breastfeeding is associated with allergic rhinitis with a p <0.05; mixed lactation with 64% and artificial lactation with 83.6% and those who consumed breastfeeding and had allergic rhinitis was 6.3% with an OR = 0.61 thus obtaining a protective factor. For complementary feeding, there was no association with allergic rhinitis, obtaining a p-value = 0.791 and an OR = 1.15, thus considering it a risk for allergic rhinitis. Conclusions: it is determined that environmental factors (family history, breastfeeding) are associated with allergic rhinitis, there is significant evidence of the association (p <0.05), which indicates that there is a risk factor for allergic rhinitis.